2014
DOI: 10.1002/jmri.24715
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous contrast MRI of cardiac fibrosis: Beyond late gadolinium enhancement

Abstract: The aim of this review is to provide an overview of detection of cardiac fibrosis with MRI using current standards and novel endogenous MRI techniques. Assessment of cardiac fibrosis is important for diagnosis, prediction of prognosis and follow-up after therapy. During the past years, progress has been made in fibrosis detection using MRI. Cardiac infarct size can be assessed noninvasively with late gadolinium enhancement. Several methods for fibrosis detection using endogenous contrast have been developed, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 68 publications
(77 reference statements)
0
29
0
Order By: Relevance
“…In addition novel magnetic resonance techniques with or without using contrast agents look promising for cardiac fibrosis detection. 23 We observed that in the LV posterolateral wall the pattern of fibrosis and fatty changes is highly distinctive for groups of mutations. Therefore, the present study may provide a roadmap for further in vivo cardiac fibrosis assessment in patients.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition novel magnetic resonance techniques with or without using contrast agents look promising for cardiac fibrosis detection. 23 We observed that in the LV posterolateral wall the pattern of fibrosis and fatty changes is highly distinctive for groups of mutations. Therefore, the present study may provide a roadmap for further in vivo cardiac fibrosis assessment in patients.…”
Section: Discussionmentioning
confidence: 68%
“…On average the hearts with a desminopathy (25% [24][25][26]) and the hearts with a p. Arg14del PLN mutation (25% [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]) had the most fibrosis, followed by the sarcomeric gene mutations (20% [16-28]), desmosomal mutations (17% [14][15][16][17][18][19][20][21][22][23][24][25][26]) and the lamin A/C mutations (14% ; p=0.67 between mutation groups; p<0.001 for control versus cardiomyopathy).…”
Section: The Total Amount Of Fibrosismentioning
confidence: 99%
“…Furthermore, the calculation of an ECV‐map requires the acquisition of two different T 1 ‐maps, one before and one 15–20 min after contrast injection, which requires a long scan time. These drawbacks can potentially be overcome when endogenous MRI contrast mechanisms are used to detect myocardial fibrosis …”
mentioning
confidence: 99%
“…These drawbacks can potentially be overcome when endogenous MRI contrast mechanisms are used to detect myocardial fibrosis. 9 A promising endogenous MRI contrast mechanism to measure myocardial fibrosis is T 1q -MRI. The T 1q -relaxation time describes relaxation while the magnetization is in the transverse plane, in the presence of a so-called SL radiofrequency (RF) pulse.…”
mentioning
confidence: 99%
“…In the specific case of diffuse myocardial fibrosis, T1 mapping is considered as superior to the highly invasive and partial endomyocardial biopsies and the indirect technique of LGE. Indeed, it provides a quantitative T1 relaxation time per voxel, instead of a qualitative T1 contrast, allowing discrimination of remaining healthy areas [156].…”
Section: T1 Mappingmentioning
confidence: 99%